Topics in Modal Analysis, Volume 7 Proceedings of the 31st IMAC, A Conference on Structural Dynamics, 2013 - Allemang, Randall; De Clerck, James; Niezrecki, Christopher; Wicks, Alfred; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Topics in Modal Analysis, Volume 7:  Proceedings of the 31st IMAC, A Conference and Exposition on Structural Dynamics, 2013, the seventh volume of seven from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on:   Fluid Structure Interaction Adaptive Structures Experimental Techniques Analytical Methods Damage Detection Damping of Materials & Members Modal Parameter Identification Modal Testing Methods System Identification Active Control Modal Parameter Estimation Processing Modal Data.
From the Contents: Damage Detection Using Flexibility Proportional Coordinate Modal Assurance Criterion -- Automated Selection of Damage Detection Features by Genetic Programming -- Optimal Selection of Artificial Boundary Conditions for Model Update and Damage Detection - Part 1:Theory -- Optimal Selection of Artificial Boundary Conditions for Model Update and Damage Detection - Part 2: Experiment -- Detection of Mass Change on a Glass Plate -- Vibro-acoustic Research on a Full-scale Aircraft Structure -- Control of Dynamic Mass as Boundary Condition for Testing Substructures -- Multi-body-simulation of a Self Adaptive Torsional Vibration Absorber.
Keywords: Vibration; Dynamical systems; Dynamics; Aerospace engineering; Astronautics; Mechanics; Mechanics, Applied; Vibration, Dynamical Systems, Control; Aerospace Technology and Astronautics; Solid Mechanics